Quality in Management: Process Management, Activity-Based Costing, and the Balanced Scorecard - Ugalde Binda, Nadia (2011)
The global competition has impelled companies to evaluate its internal processes and to have an absolute clarity on its operations literature aims, among other things, at the use of consolidated and strategic information systems together with the administration by processes (BPM of Business Process Management) Two of the most known systems are acrivity-Based costing (aBc) and the balance scored card (BSc). Thus, the objective of this theoretical investigation is to establish the form in which the approaches of aBc, BSc, and BPM are complementary and to synthesize their main contributions.